Simultaneous Switching Noise Impact To Signal Sensitivity On Usb 2.0 - Chan, Siang Rui (2013)
Simultaneous Switching Noise (SSN) is increasing with higher I/O data rate, resulting into challenges for regulating supply voltage in typical transistor circuit. Supply voltage changes accordingly with Power Distribution Network (PDN) design. Engineering efforts are focused on PDN layout to minimize the impedance path. However, the desire to miniaturize components on a system increases design challenges to control voltage drop via comprehensive PDN design. Hence, it is a need to study the impact of supply noise to signal performance in future PDN design. Instead of optimizing PDN, a different way of quantifying different frequency supply voltage impact to output signal is introduced in this research. In order to observe this relationship, Universal Serial Bus (USB) transmitter circuit signal performance is explored. Signal eye diagram is observed by replacing DC input voltage with various frequencies of AC input voltage. From the simulation, USB transmitter has better immunity to the supply noise at its operating frequency of 480 MHz, and also its harmonic frequencies of 960 MHz and 1.44 GHz. Excessive amount of supply noises at these frequencies are not causing signal eye diagram to fail. This finding is further verified by lab measurement. Eye diagram is measured by different simultaneous switching stress test cases. The supply voltage is captured and analyzed using Fast Fourier Transform (FFT) to identify the major frequency contributors in the noise profile. From the measurement result, signal has better performance especially when the measured supply noise falls in the frequency regions of 480 MHz and 960 MHz.